Using Mark Chagall’s Visual Art in Teaching Visual Arts - Kuščević, Dubravka; Brajčić, Marija; Šipić, Luce (Revija za elementarno izobraževanje, 2019)
This paper focuses on the importance of visual arts in the education of students, while also analyzing the need for using a work of visual art as material in teaching visual arts. The works of Marc Chagall, one of the most significant artists of the 20th century, were chosen for the purpose of the research. The aim of the paper was to reveal the visual and verbal reactions of students to the works of Marc Chagall in teaching visual arts, using the method of aesthetic transfer and game activities during contact between the students and the artworks. For this purpose, we conducted a study involving students in the first and third grades of the “Spinut” primary school in Split, the Republic of Croatia. Based on the works they made, we confirmed the hypotheses that students would gladly accept the works of Marc Chagall and successfully express themselves when inspired by this artist.
Keywords: visual arts; teaching visual arts; artwork; Marc Chagall